Influence of Fetuin-A on Chlamydia muridarum Pulmonary Infection - Mahjabeen, Faria; Yu, Jieh-Juen; Chambers, James P.; Gupta, Rishein; Arulanandam, Bernard P. (International Journal of Microbiology, 2022)
Fetuin-A is an acute phase glycoprotein shown to counter in a regulatory manner proinflammatory cytokine production to maintain homeostasis during inflammation. We report here that in wild-type mice 12 days after Chlamydia muridarum (Cm) intranasal challenge, fetuin-A content in the lungs decreased 46%, while INF-γ increased 44%, consistent with a negative regulatory role of fetuin-A in inflammation. Importantly, the observed increased IFN-γ production was abrogated in fetuin-A-deficient AHSG mice suggesting that IFN-γ induction following Cm infection is fetuin-A dependent. Assessment of expression of genes associated with inflammation revealed fetuin-A-dependent upregulation of TBX21 (a Th1 cell-specific transcription factor) in the lungs of Cm-infected WT mice that correlated with IFN-γ induction. Additionally, the effect of fetuin-A deficiency in mounting an adaptive immune response to Cm infection was demonstrated using a splenocyte recall assay. Although preliminary in nature, these findings are suggestive of fetuin-A involvement following Cm pulmonary infection and underscores the need to investigate further the role of fetuin-A in the immune response and the consequences of its gene deletion.